THE IMAGE OF A ‘DRUNKEN SCYTHIAN’ IN GREEK TRADITION - Porucznik, Joanna (European Scientific Journal, ESJ, 2013)
Since the Greeks first came into contact with Scythian populations (who should be understood as a great conglomerate of various groups of peoples inhabiting the north Pontic steppes), many negative clichés concerning the Scythians occurred in Greek tradition. One of them is the stereotype of drunkenness among the Scythians and their lack of urbane manners that were commonly accepted by Greek society. This image of a drunken Scythian may have been created in Greek tradition due to the fact that the Scythians (Scythian aristocracy in particular) adopted the Greek tradition of the drinking of wine. This is visible in archaeological material from the northern Black Sea areas, where many amphorae and wine jars have been found in Scythian tombs. However, written sources indicate that the Scythians did not mix wine with water and this did not correspond with Greek customs, according to which drinking unadulterated wine was extremely ‘barbarian’ and inappropriate. This in turn may have become a catalyst behind the concept of drunkenness amongst the Scythians.